Transfer of shrines in pre-mongolian Rus: the calendar-related aspect of the ceremonies - Aleksei Laushkin (Vestnik Pravoslavnogo Svâto-Tihonovskogo Gumanitarnogo Universiteta: Seriâ II. Istoriâ, Istoriâ Russkoj Pravoslavnoj Cerkvi)
The Church calendar in Old Rus' did not only determine the course of divine services, but also actively influenced the planning of the most important events by princes and bishops, both ecclesiastical and secular. The timing of the ceremonies (that framed such events) to significant festive milestones of liturgical cycles, besides the utilitarian and symbolic meanings, carried an important spiritual content. As the organizers see it, calendar timing was a means of special turning to God and the saints. A clear dependence on the calendar is demonstrated, in particular, by the chronological component of the celebrations dedicated to the transfer of shrines. The article clarifies and analyzes all the exact (daily) dates of such events of the 11th – the first third of the 13th centuries preserved in the sources. In total, ten such dates have come down to us: four of them relate to the relocation of the relics of sts. Boris and Gleb, the remaining six – of other Russian and imported relics. The author of the article comes to the conclusion that the organizers of the celebrations used several calendar strategies, and usually layered them on top of each other, striving to achieve what can be called “multiplication of festivity”. In most cases, the transfer of shrines turned out to be correlated with Sundays and at the same time coordinated with the rhythms of the Menologion and the Triodion: the “liturgical fields” of Easter and great feasts and (or) calendar milestones associated directly with the honored saint. The obtained results complement the scientific understanding of the temporal culture and eorthological creativity of the Old Rus' elite.